Viabilitas Spermatozoa Ayam Hutan Hijau dalam Pengencer Posfat Kuning Telur Ditambah Laktosa pada Penyimpanan 5oC (GREEN JUNGGLE FOWL SPERM VIABILITY IN EGG YOLK PHOSFAT DILUENTS CONTAINING LACTOSE STORAGED AT 5OC) - Bebas, Wayan; Laksmi, Desak Nyoman Dewi Indira (Jurnal Veteriner, 2015)
The objective of this study was to determine the addition of lactose on egg yolk phosphate diluentsstored at 5°C to the plasma membrane intact, acrosome membranes intact of green jungle fowlspermatozoa, fertility and hatchability of chicken eggs. This study used completely randomized designwith three treatment groups. Treatment I (T0): egg yolk phosphate diluents only (control), treatment II(T1): egg yolk phosphate diluents + lactose 0.3%, and treatment III (T2): egg yolk phosphate diluents +lactose 0.6 %. Each group was replicated nine times. Semen was collected from eight green jungle fowl andevaluated both macroscopically and microscopically. Semen was diluted with each treatment with a singleinsemination dose (0.5 mL) with a concentration of 150 million progressively motile cells. Once diluted,semen was stored at 3-5°C for 48 hours and then was observed for the plasma membrane of intact,acrosome membrane of intact, and some semen were inseminated on local female chicken village forfertility, and hatchability eggs observation. The results showed that the addition of lactose 0.3% and 0.6%providing significant increase (P <0.05) on plasma membrane intact, acrosome membrane intact, fertilityand egg hatchability when compared to controls. However the addition of 0.3% and 0.6% lactose did notshowed a significant effect (P> 0.05). This study concluded that the addition of lactose on egg yolk phosphatediluents for storing green jungle fowl spermatozoa at 3-5oC for 48 hours can improve the plasma membraneintact, acrosome membranes intact, fertility and hatchability of chicken eggs.
Keywords: lactose, plasma membrane intact, acrosome membrane intact, green jungle fowl spermatozoa